AQ-3 Profile Cortisol, Neutrophyle/Lymphocyte Ratio and IL-6 on Bali Cattle Transported by Traditional Vessel during 120 Hours - Hindar Panguji; Niqlah Rifqiyah (Hemera Zoa, 2018)
Transportation of livestock using wooden vessels is frequently used fulfilling the demand of another Province on Bali cattle. Cattle transportation arranged in the Office Internationale Epizooticae (OIE) and the Internatinal Air Transport Association (IATA) is highly susceptible to stress. This study aims to determine the profile of hormones cortisol, neutrophyle/lymphocyte ratio and IL-6 as stress indicator.